Understanding data communications : from fundamentals to networking. - Held, Gilbert, 1943- (Chichester : Wiley, 2001)
Now in its third edition, Understanding Data Comunications, provides a comprehensive introduction to the field of data communications for both students and professionals. Assuming no prior knowledge of the field, it presents an overview of the role of communications, their importance, and the fundamental concepts of using the ISO's 7-layer approach to present the various aspects of networking. * Covers the evolving high speed network access via digital subscriber line, cable modems and wireless communication. * Examines the role of regulatory and standardization bodies, the operation of the Internet and the use of a variety of electronic applications. * Includes a series of comprehensive questions covering the important concepts from each section. * Describes the digital network used by communications carriers and the methods used to obtain access to the digital highway. * Discusses frequency division multiplexing which forms the foundation for the operation of several types of high speed digital subscriber line. Aimed at the senior level undergraduate and graduate computer science student, it is also essential reading for data processing professionals and those involved in computer science and data communications.